School days - Hennessy, B. G. (Barbara G.); Pearson, Tracey Campbell (New York, N.Y., U.S.A. : Viking, 1990)
Rhyming text and illustrations describe the familiar faces and objects of a day at school.
"Ages 3-8"--Jacket.
Children's Catalog (Wilson)
Elementary School Library Collection (Bro-Dart)
Booklist
1.4
K-3
Keywords: Schools -- Fiction; Stories in rhyme; Stories in rhyme; School stories